KESALAHAN GRAMATIKAL BAHASA INGGRIS PADA PENJABARAN GRAFIK DALAM MATA KULIAH BAHASA INGGRIS 1 - Yessy Purnamasari; Danny Gandana Nugraha (Jurnal Bahasa Lingua Scientia, 2023)
In learning English, the learners make some common mistakes in applying the correct grammar. One of the mistakes is the error in explaining graphs in English. This competency is highly needed to be applied in many aspects, especially for vocational university students. For example, explaining a chart in English is somehow mandatory in composing a budget or presenting a project to a client. Thus, this study is aimed to identify the types of grammatical errors typically done by the learners. By applying the descriptive qualitative methodology, the 30 data used in this study are taken from the sample of students’ writing in explaining a chart in English. The steps taken are done by doing data categorization based on Dulay’s surface strategy taxonomy which mentions four types of errors: addition, omission, misformation, and misordering. The results show that omission is the type of error mostly done by learners with 34,78%, followed by addition with 31,88% occurrence, and the least error found in the data is misorder with 10,14%. It is suggested that students should be equipped with basic Grammar understanding in explaining a graph in English, so this kind of error will be minimized. This study is also expected to give insight to lecturers in composing the General English syllabus that emphasizes the student’s understanding of basic Grammar.